2015
DOI: 10.1371/journal.pone.0125599
|View full text |Cite
|
Sign up to set email alerts
|

Protein Degradation of RNA Polymerase II-Association Factor 1(PAF1) Is Controlled by CNOT4 and 26S Proteasome

Abstract: The PAF complex (PAFc) participates in various steps of the transcriptional process, from initiation to termination, by interacting with and recruiting various proteins to the proper locus for each step. PAFc is an evolutionarily conserved, multi-protein complex comprising PAF1, CDC73, CTR9, LEO1, yRTF1 and, in humans, hSKI8. These components of PAFc work together, and their protein levels are closely interrelated. In the present study, we investigated the mechanism of PAF1 protein degradation. We found that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The E3 ubiquitin ligase Not4/Mot2 has various functions in protein metabolism. Previous work showed that Mot2 controls protein turnover through ubiquitination and proteasome-dependent degradation to regulate chromatin modification, DNA replication, transcription as well as translation ( Panasenko et al, 2006 ; Laribee et al, 2007 ; Mersman et al, 2009 ; Haworth et al, 2010 ; Cooper et al, 2012 ; Sun et al, 2015 ; Laribee et al, 2015 ; Brönner et al, 2017 ). Other studies revealed roles in the functional integrity of the proteasome ( Panasenko and Collart, 2011 ) and in translational quality control ( Dimitrova et al, 2009 ; Halter et al, 2014 ; Preissler et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The E3 ubiquitin ligase Not4/Mot2 has various functions in protein metabolism. Previous work showed that Mot2 controls protein turnover through ubiquitination and proteasome-dependent degradation to regulate chromatin modification, DNA replication, transcription as well as translation ( Panasenko et al, 2006 ; Laribee et al, 2007 ; Mersman et al, 2009 ; Haworth et al, 2010 ; Cooper et al, 2012 ; Sun et al, 2015 ; Laribee et al, 2015 ; Brönner et al, 2017 ). Other studies revealed roles in the functional integrity of the proteasome ( Panasenko and Collart, 2011 ) and in translational quality control ( Dimitrova et al, 2009 ; Halter et al, 2014 ; Preissler et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Post-translational modifications of histones such as acetylation, phosphorylation, methylation, ubiquitylation and SUMOylation can affect the properties of chromatin to enhance or suppress gene transcription (36). The ubiquitin-proteasome pathway has been suggested to be involved in elongation phase of transcription to chromatin remodeling/modification; (37) and also in protein degradation of unbound RNA polymerase II associated factor (38). Therefore, downregulation of proteasome's proteases can have a profound effect on gene expression via histone modification, chromatin remodeling and RNA polymerase II associated factor.…”
Section: Discussionmentioning
confidence: 99%
“…Not4 appears to contribute to different aspects of transcription from initiation to elongation. It indirectly controls histone H3K4 tri-methylation, an active marker of transcription, by two mechanisms: firstly, by regulating the activity of the PAF1 complex (PAF1C), on the one hand, by facilitating the loading of PAF1C on to promoters and, on the other hand, by ubiquitin-dependent proteolysis of PAF1 not bound to chromatin through the 26S proteasome [166,206]. Set1-directed methylation of H3K4 depends on the PAF1C-dependent ubiquitylation of H2B [207].…”
Section: The Ccr4-not Complex and Transcriptionmentioning
confidence: 99%